Aplikasi Ca(OH)2 Untuk Limbah Kegiatan Pickling dengan Metode Netralisasi dan Presipitasi - Astri Rino Okvitasari (Techno Bahari, 2022)
Pickling activity is a process of washing stainless steel pipes to remove impurities attached to the pipes. The pickling solution is made of acidic substances, so the end result of the pickling activity produces waste called water rinse. Water rinse can still be disposed of into the WWTP water bodies in industrial areas, as long as it meets the quality standards. The use of the neutralization and precipitation methods using Ca(OH)2 agent of 0.56 kg/day for the capacity of 1 tub of water rinse with a volume of 2,043 m3 is able to provide a percentage removal of Fe as much as 100%, Cr 100%, and Ni 99.99%. Where in this method produces as much as 574.10 grams of sludge every day which contains heavy metals.